Total, matric and osmotic suction measurement of compacted soils - Cui, Xiao (2017)
Compacted soils are unsaturated and has total suction which consists of matric and osmotic suctions. The objective of this project is to measure the three types of suctions of soils compacted by different Proctor efforts and assess the interrelations between the three measurements. In this project, total suction is measured by chilled mirror dew point device and the non-contact filter paper method. Matric suction is measured by in-contact filter paper method and the osmotic suction is measured by the pore-fluid squeezer method. The results showed that the sum of matric and osmotic suction is lower than the measured total suction for samples mixed with tap water for both compaction efforts and that the compaction effort did not make an apparent difference to the measured suctions.